Placenta accreta spectrum disorder in a primigravida with angular pregnancy: a case report (Medical Journal of Indonesia, 2022)
Placenta accreta spectrum (PAS) is characterized by abnormal invasion of placental tissue into the underlying uterine muscles and has an incidence of 1/533–1/251. The incidence of complications includes uterine rupture (14–29%), PAS (6–10%), and retained placenta or incomplete placenta removal (4%). Here, we described a rare case of PAS and angular pregnancy, including how to diagnose and manage it preoperatively. A 32-year-old primigravida diagnosed at 24 weeks of gestation with a right angular pregnancy was admitted due to preterm premature rupture of membrane (PPROM) with a singleton fetus. We decided to perform hysterotomy because of the PPROM and intrauterine infection. Intraoperatively, we found PAS in the right angular pregnancy; therefore, we performed uterine conservative management with wedge resection on the right uterine fundus. Intraoperative bleeding was 1,600 cc. Histopathological examination revealed placenta increta. The maternal prognosis was good, while the fetus was poor, with an APGAR score of 1/1/0.